Ways of Following: Art, Materiality, Collaboration - Katve-Kaisa Kontturi (Open Humanities Press, 2022)
In Ways of Following, Katve-Kaisa Kontturi offers rare, intimate access to artists’ studios and exhibitions, where art processes thrive in their material-relational becoming. The book argues for an ethical and affirmative mode of engaging with contemporary art that replaces critical distance with sensuous and transformative proximity. From writing-with to dancing and breathing, from conversations to modelling, it maps ways of following that make the moving materiality of art intensively felt. Drawing on long-term engagements with selected contemporary artists and their art-in-process, Kontturi expands the concept and practice of collaboration from human interactions to working with, and between, materials. With this shift, Ways of Following radically rethinks such core tenets of art theory as intention, artistic influences and the autonomy of art, bringing new urgency to the work of art and its political capacity to propose new ways of being and thinking.